Effectiveness of Robot-Assisted Upper Extremity Function Training (Gloreha) on Upper Extremities Function After Stroke: Systematic Review - Chirathip Thawisuk; Sopida Apichai; Waranya Chingchit; Jananya P Dhippayom; Teerapon Dhippayom (JMIR Rehabilitation and Assistive Technologies)
Abstract BackgroundThe Gloreha (Idrogenet SRL) is a robotic device that enhances conventional rehabilitation for improving upper extremity function after stroke, but comprehensive evidence on its effectiveness is still lacking. ObjectiveThe objective of this study was to evaluate the effectiveness of the Gloreha device on upper extremity function and activities of daily living (ADLs) in patients with stroke. MethodsPubMed, Cochrane CENTRAL, CINAHL, Embase, and EBSCO Open Dissertations were searched from January 2013 to January 2024. The inclusion criteria were randomized controlled trials involving adult patients with stroke that compared rehabilitation with the Gloreha device to conventional rehabilitation and reported upper extremity function or ADLs outcomes. All included studies underwent bias risk assessment using the Revised Cochrane risk-of-bias tool for randomized trials. ResultsOut of 1123 studies identified, 3 randomized controlled trials involving 83 participants were included. Of these, 2 trials combined Gloreha training with conventional rehabilitation, while in another trial, patients engaged solely in the training by the Gloreha device. The Gloreha, whether integrated with conventional rehabilitation or used independently, has the potential to enhance motor function and functional ability in survivors of stroke. ConclusionsGloreha passive training with conventional rehabilitation improves upper extremity function post stroke, but ADL effects and long-term optimal dosing require further research.